Human Capital and Organizational Justice as Stimulant of Innovative Behavior to Achieve Managerial Performance - Ridwan, Wildan; Daromes, Fransiskus Eduardus; Sampe, Ferdinandus (AJAR, 2025)
This study aims to provide empirical evidence on how Human capital and organizational justice may influence managerial performance directly and through innovative behavior. The research model was constructed using the organizational justice Theory perspective. The research population was account representatives at all Primary Tax Service Offices in South Sulawesi. Purposive sampling method was applied to determine respondents for data collection. The data collection method was carried out through an online survey. Data analysis were carried out using multiple regression and path analysis. The results of the study indicate that both Human capital and organizational justice have significant effect on innovative behavior. Furthermore, Human capital has a significant effect on managerial performance. However, conversely, organizational justice does not have a significant effect on managerial performance. Further findings reveal that innovative behavior mediates the influence of both Human capital and organizational justice on managerial performance.